Association of puberty timing with type 2 diabetes: A systematic review and meta-analysis. - Tuck Seng Cheng; Felix R Day; Rajalakshmi Lakshman; Ken K Ong (PLoS Medicine)
Background Emerging studies have investigated the association between puberty timing, particularly age at menarche (AAM), and type 2 diabetes. However, whether this association is independent of adiposity is unclear. We aimed to systematically review published evidence on the association between puberty timing and type 2 diabetes (T2D) or impaired glucose tolerance (IGT), with and without adjustment for adiposity, and to estimate the potential contribution of puberty timing to the burden of T2D in the United Kingdom (UK). Methods and findings We searched PubMed, Medline, and Embase databases for publications until February 2019 on the timing of any secondary sexual characteristic in boys or girls in relation to T2D/IGT. Inverse-variance-weighted random-effects meta-analysis was used to pool reported estimates, and meta-regression was used to explore sources of heterogeneity. Twenty-eight observational studies were identified. All assessed AAM in women (combined N = 1,228,306); only 1 study additionally included men. In models without adjustment for adult adiposity, T2D/IGT risk was lower per year later AAM (relative risk [RR] = 0.91, 95% CI 0.89-0.93, p < 0.001, 11 estimates, n = 833,529, I2 = 85.4%) and higher for early versus later menarche (RR = 1.39, 95% CI 1.25-1.55, p < 0.001, 23 estimates, n = 1,185,444, I2 = 87.8%). Associations were weaker but still evident in models adjusted for adiposity (AAM: RR = 0.97 per year, 95% CI 0.95-0.98, p < 0.001, 12 estimates, n = 852,268, I2 = 51.8%; early menarche: RR = 1.19, 95% CI 1.11-1.28, p < 0.001, 21 estimates, n = 890,583, I2 = 68.1%). Associations were stronger among white than Asian women, and in populations with earlier average AAM. The estimated population attributable risk of T2D in white UK women due to early menarche unadjusted and adjusted for adiposity was 12.6% (95% CI 11.0-14.3) and 5.1% (95% CI 3.6-6.7), respectively. Findings in this study are limited by residual and unmeasured confounding, and self-reported AAM. Conclusions Earlier AAM is consistently associated with higher T2D/IGT risk, independent of adiposity. More importantly, this research has identified that a substantial proportion of T2D in women is related to early menarche, which would be expected to increase in light of global secular trends towards earlier puberty timing. These findings highlight the need to identify the underlying mechanisms linking early menarche to T2D/IGT risk.